Quranic Interpretation And Its Discourse: The Case Of Naṣr Hamīd Abū Zayd Commentary In Between Tafsīr And Ta’wīl - Jamaluddin Akbar; Zainul Arif; Ulya Darojah; M. Khodimul Wahib (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the interpretive discourse of Naṣr Ḥamīd Abū Zayd concerning the relationship between tafsīr and ta’wīl within contemporary Qur’ānic hermeneutics. Employing a non-empirical qualitative design, the research applies textual and qualitative content analysis to Abū Zayd’s major works, Mafhūm al-Naṣṣ: Dirāsah fī ‘Ulūm al-Qur’ān and al-Tajdīd wa al-Taḥrīm wa al-Ta’wīl: Bayna al-Ma‘rifah al-‘Ilmiyyah wa al-Khawf min al-Takfīr. The analysis explores how interpretive terminology, authority, and textual meaning are constructed within the broader intellectual history of Qur’ānic interpretation. The findings indicate that Abū Zayd reconceptualizes ta’wīl as a critical hermeneutical practice that mediates between linguistic textuality, historical context, and human reasoning. Rather than rejecting the classical exegetical tradition, his framework situates tafsīr and ta’wīl within a complementary interpretive continuum. This reconstruction challenges rigid interpretive hierarchies and highlights the discursive nature of Qur’ānic interpretation. The study demonstrates that Abū Zayd’s hermeneutical project contributes to contemporary debates on interpretive authority, contextual reading, and methodological pluralism in Qur’ānic studies, offering a conceptual model that bridges classical exegetical heritage with modern intellectual inquiry.